Injectable gentamicin-loaded thermo-responsive hyaluronic acid derivative prevents infection in a rabbit model. (1st October 2016) - ter Boo, Gert-Jan A.; Arens, Daniel; Metsemakers, Willem-Jan; Zeiter, Stephan; Richards, R. Geoff; Grijpma, Dirk W.; Eglin, David; Moriarty, T. Fintan
Graphical abstract: Abstract: Despite the use of systemic antibiotic prophylaxis, the surgical fixation of open fractures with osteosynthesis implants is associated with high infection rates. Antibiotic-loaded biomaterials (ALBs) are increasingly used in implant surgeries across medical specialties to deliver high concentrations of antibiotics to the surgical site and reduce the risk of implant-associated infection. ALBs which are either less or not restricted in terms of spatial distribution and which may be applied throughout complex wounds could offer improved protection against infection in open fracture care. A thermo-responsive hyaluronic acid derivative (hyaluronic acid-poly( N -isopropylacrylamide) (HApN)) was prepared by a direct amidation reaction between the tetrabutyl ammonium (TBA) salt of hyaluronic acid and amine-terminated poly( N -isopropylacrylamide) (pN). The degree of grafting, and gelation properties of this gel were characterized, and the composition was loaded with gentamicin. The rheological- and release properties of this gentamicin-loaded HApN composition were tested in vitro and its efficacy in preventing infection was tested in a rabbit model of osteosynthesis contaminated with Staphylococcus aureus . The gentamicin-loaded HApN composition was able to prevent bacterial colonization of the implant site as shown by quantitative bacteriology. This finding was supported by histopathological evaluation of the humeri samples where no bacteria were found in the stained sections. In conclusion, this gentamicin-loaded HApN hydrogel effectively prevents infection in a complex wound, simulating a contaminated fracture treated with plating osteosynthesis. Statement of Significance: Fracture fixation after trauma is associated with high infection rates. Antibiotic loaded biomaterials (ALBs) can provide high local concentrations without systemic side effects. However, the currently available ALBs have limited accessibility to contaminated tissues in open fractures because of predetermined shape. Thus, a novel thermo-responsive hyaluronan based hydrogel with control over gelation temperature is reported. The efficacy of this gentamicin loaded hyaluronan derivative is demonstrated in an in vivo fracture model in the presence of fracture fixation hardware. The bacterial burden is cleared in all of the inoculated rabbits in the presence of the ALB. Thus, the proposed injectable thermo-responsive hyaluronan presents an effective ALB for the prevention of infection.